Obtaining for Waiting Times at Centers of Light on a Reinforced Concrete Bridge simply supported by a 30m-long Single Board and Slab Beam, Using Traffic Centers through Simulation - Vanegas, Sergio; Chio, Gustavo (Ingeniería Solidaria, 2014)
This article gives the results of calculating waiting times in the center of an internal beam of a 30 m long bridge, simply supported in reinforced concrete and a beam and ceramic board, over which randomly organized trucks pass, using a Weekly Average Daily Traffic (tpds from its Spanish acronym) count. To make this calculation, the lines of influence methodology for a simply-supported beam is used. The trucks cross the bridge at intervals of 0.1 m, which is the precision used. At each instant, the forces produced by the weight of the truck wheels are calculated, plus the weight of the elements (beams and slabs), randomly applying certain properties of the materials with normal distribution (, and density of the concrete). This procedure is simply a Monte Carlo simulation. The dimensions of the bridge on which the calculations were made were obtained using a design methodology from the Colombian Seismic Bridge Design Code (Código Colombiano de Diseño Sísmico de Puentes, ccdsp-95). The study was carried out in 2013 by the Universidad Industrial de Santander (uis).